Intimate Partner Violence Among Women of Reproductive Age in Nicaragua: Results From a Nationwide Survey - Hernández-Vásquez, Akram (Journal of interpersonal violence, 2022)
This article aims to identify the factors associated with intimate partner violence (IPV) using data from the latest available nationwide survey in Nicaragua. A secondary analysis of the 2011?2012 Nicaraguan Demography and Health Survey (ENDESA 2011?2012) was conducted. A total of 12,605 women aged 15?49 years who had reported being married or united were included. IPV (yes/no) was defined as the outcome variable, and it was considered if a woman suffered verbal, psychological, physical, or sexual violence during the previous 12 months. Crude and adjusted odds ratios with 95% CI were calculated using a bivariate and multivariate logistic regression model. A p value <.05 was considered statistically significant and did not correct p values for multiple testing. The overall prevalence of IPV was 17.5%. Women living in urban setting (AOR: 1.51, 95% CI: 1.26?1.80), women who self-identify as native (AOR: 1.34, 95% CI: 1.34?1.61) or women who have a history of abuse as a child (AOR: 1.96, 95% CI: 1.69?2.27) were more likely to suffer IPV compared to their counterparts. Age was found to be a protective factor for IPV. Variables such as educational level and wealth index, do not report any association with IPV. Our findings shows that IPV in Nicaragua continues to be a frequent event. The results provide evidence of drivers for IPV at a national level. These findings are useful for the design of intervention policies and strategies for the prevention of IPV.